Differential regulation of reactive oxygen species in dimorphic chloroplasts of single cell C4 plant Bienertia sinuspersici during drought and salt stress - Uzilday, Baris; Ozgur, Rengin; Yalcinkaya, Tolga; Sonmez, Mustafa Cemre; Turkan, Ismail (Frontiers in Plant Science, 2023)
Single cell C4 (SCC4) plants, discovered around two decades ago, are promising materials for efforts for genetic engineering of C4 photosynthesis into C3 crops. Unlike C4 plants with Kranz anatomy, they exhibit a fully functional C4 photosynthesis in just a single cell and do not require mesophyll and bundle sheath cell spatial separation. Bienertia sinuspersici is one such SCC4 plant, with NAD-malic enzyme (NAD-ME) subtype C4 photosynthesis. Its chlorenchyma cell consist of two compartments, peripheral compartment (PC), analogous to mesophyll cell, and central compartment (CC), analogous to bundle sheath cell. Since oxidative stress creates an important constraint for plants under salinity and drought, we comparatively examined the response of enzymatic antioxidant system, H2O2 and TBARS contents, peroxiredoxin Q, NADPH thioredoxin reductase C, and plastid terminal oxidase protein levels of PC chloroplasts (PCC) and CC chloroplasts (CCC). Except for protein levels, these parameters were also examined on the whole leaf level, as well as catalase and NADPH oxidase activities, water status and growth parameters, and levels of C4 photosynthesis related transcripts. Many C4 photosynthesis related transcript levels were elevated, especially under drought. Activities of dehydroascorbate reductase and especially peroxidase were elevated under drought in both compartments (CCC and PCC). Even though decreases of antioxidant enzyme activities were more prevalent in PCC, and the examined redox regulating protein levels, especially of peroxiredoxin Q, were elevated in CCC under both stresses, PCC was less damaged by either stress. These suggest PCC is more tolerant and has other means of preventing or alleviating oxidative damage.